Survey of Facilities and Infrastructure for Enhancing Physical Education and Sports Capabilities at SMA 3 Boyolali. - Gilang Prayoga,; Dewangga Prada, Bajalagha; Junianto, Sefen; Panca Aji, Arya; Prabuwana Dewa, Armada; Sakti Rumpoko, Satrio (Universitas Tunas Pembangunan Surakarta, 2024)
Survey on the Facilities and Infrastructure of Physical Education, Sports, and Health at SMA Negeri 3 Boyolali.